Ranked Set Sampling Model for Response Estimation of Developmental Programs with Exponential Impacts - Neeraj Tiwari; Girish Chandra; Shailja Bhari (Journal of the Indian Society of Agricultural Statistics, 2025)
Government and non-government organizations regularly initiate developmental programs in successive phases. Each phase plays a significant role in the development process. These programs aim to enhance the socio-economic conditions of communities and individuals by addressing issues such as poverty ,health, education, women empowerment, and infrastructure. Every year, many such programs are implemented in several areas for various purposes, including health awareness programs, women empowerment programs, cleanliness programs, vaccination campaigns, and educational programs to improve health and public participation. Chandra et al. (2018a) considered the linear impact of programs across successive phases and used a multiplicative model that linked with predefined survey and response variables. They employed the model to estimate the population mean of the response variable using the Ranked Set Sampling (RSS) on the survey variable, which led to the linear impact valuation of developmental programs. In this paper, we have suggested an exponential impact to reflect more realistic growth patterns in numerous development processes. We have proposed an estimator of the response variable under RSS based on the survey variable with exponential impact and compared to an estimator of RSS with Linear impact in terms of relative precision (RP). The pattern of various RPs is explored using the real-life example of Education for all towards quality with equity.